1991
DOI: 10.1039/c39910000946
|View full text |Cite
|
Sign up to set email alerts
|

Push–pull carbenes: methoxytrifluoromethylcarbene

Abstract: Despite the possibility of 'push-pull' carbene stabilization by su bstituents of opposing electronic properties, absolute rate studies show methoxytrifluoromethylcarbene to be highly reactive and electronically indiscriminant in its reactions with alkenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 11 publications
0
27
1
Order By: Relevance
“…Likewise, other strongly electron‐withdrawing groups such as CF 3 should show similar rehybridization effects. Others have noted the possible influence of the CF 3 inductive effect on singlet carbene stability, including in combination with other stabilizing groups …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, other strongly electron‐withdrawing groups such as CF 3 should show similar rehybridization effects. Others have noted the possible influence of the CF 3 inductive effect on singlet carbene stability, including in combination with other stabilizing groups …”
Section: Methodsmentioning
confidence: 99%
“…Others have noted the possible influence of the CF 3 inductive effect on singlet carbene stability, [19,21] including in combination with other stabilizing groups. [36,37] Indeed, there are various clues that an inductively induced rehybridization effect operates in singlet CF 3 carbenes. For example, although the steric bulk of CF 3 should be greater than CH 3 , [28] calculations predict that the bond angle in the CF 3 carbene 5 (103.0 ) is somewhat smaller than that in the singlet state of CH 3 carbene 10 (105.9 ).…”
mentioning
confidence: 99%
“…An interesting series of catenated hydrido-metal complexes H2 [Os (CO),]., n = 1, 2, 3, and 4, is obtained in the high-pressure carbonylation of Os04 in the presence of hydrogen (194,196,197). For n = 3 and 4, these contrast both in stoichiometry and structure the triangular [H20s3(CO)1 or tetrahedral [H40s4(C0)1 2 ] complexes obtained in the direct reaction of H2 with O S~( C O )~ mentioned above.…”
Section: B Reactions With Elemental Hydrogen And/or Lowermentioning
confidence: 99%
“…In 1991, Moss and co-workers found that methoxyltrifluoromethylcarbene could react with different alkenes without significant discrimination of their electronic properties to form cyclopropanation products. 47 Inspired by these seminal work in the carbene chemistry, we further envisaged that a trifluoromethyl siloxyl carbene formed from a trifluoroacetylsilane may be a amphiphilic donoracceptor carbene, and it would undergo [2+1] cyclization reaction with various alkynes (Figure 1c).…”
mentioning
confidence: 99%